The Effect of Ratio of Red Dragon Fruit with Soursop and Agar Concentration on Quality of Slice Jam - Yolanda Maria Selina Tarigan; Ismed Suhaidi; Era Yusraini (Jurnal Rekayasa Pangan dan Pertanian, 2015)
This research was aimed to know the effect of ratio of red dragon fruit with soursop and agar concentration on the quality of slice jam. This research was conducted using a completely randomized design with two factors, namely the ratio of red dragon fruit with soursop (80%:20%, 60%:40%, 50%:50%, 40%:60, and 20%:80%) and the agar concentration (0,5%, 1%, and 1,5%). The parameters analyzed were the level of moisture content, total soluble solids, vitamin C, crude fiber content, crude pectin content, color, aroma, and texture scores and organoleptic value for color, aroma,taste,and texture. The results showed that the addition of ratio of red dragon with soursop had highly significant effect on the level of moisture content, vitamin C, crude fiber content, crude pectin content, color, texture scores and organoleptic value of color, aroma, taste, and texture. Agar concentration gave highly significant effect on level of moisture content, total soluble solids, fiber content, texture scores, organoleptic value of texture, and had significant effect of organoleptic value of taste. Interaction of the two factors gave significant effect on moisture content. Addition ratio red dragon fruit with soursop (20%:80%) and agar concentration as much as 1,5% produced the best quality of slice jam. Keywords: agar, red dragon, slice jam, soursop